Logik Wiener Logikkolleg 1894/95 - Betti, Aianna; Raspa, Venanzio (Phenomenology & Mind, 2016)
This book presents the long-awaited critical edition of an unpublished manuscript of 277 pages containing Twardowski's lecture notes on logic given in German at the University of Vienna. As to length, language and topic, this text is unique among the works of the author, who is renowned for his 'Zur Lehre vom Inhalt und Gegenstand der Vorstellungen' (1894), an influential but short book that has been out of stock for a long time already. In 'Logik' Twardowski's ideas are exposed in a much more extensive and interestingly revised form. The rest of Twardowski's production is in Polish, a language inaccessible to many readers. This edition will be of special interest to philosophers interested in the scientific philosophy in Vienna before the Wiener Kreis, to phenomenologists and anyone interested in early phenomenology and Husserl's thought, to historians of early analytic philosophy, and particularly to specialists of Austrian philosophy and the continental analytic tradition from Bolzano to Tarski, for whom the book will be a truly indispensable source.